2015
DOI: 10.1371/journal.pone.0136279
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Microbial Taxonomy Combined with Genome-Based-Approaches Reveals that Vibrio astriarenae sp. nov., an Agarolytic Marine Bacterium, Forms a New Clade in Vibrionaceae

Abstract: Advances in genomic microbial taxonomy have opened the way to create a more universal and transparent concept of species but is still in a transitional stage towards becoming a defining robust criteria for describing new microbial species with minimum features obtained using both genome and classical polyphasic taxonomies. Here we performed advanced microbial taxonomies combined with both genome-based and classical approaches for new agarolytic vibrio isolates to describe not only a novel Vibrio species but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 48 publications
1
44
0
1
Order By: Relevance
“…(41 out of 53 isolates) exhibited low percentages of identity (≤99.8%). Thus, resistant isolates were identified only to the genus level, and further analysis, such as multilocus sequence analysis (MLSA) using various housekeeping genes or whole-genome sequencing (WGS), is required to accurately define the taxonomic affiliations of Vibrio isolates, especially at the species level [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…(41 out of 53 isolates) exhibited low percentages of identity (≤99.8%). Thus, resistant isolates were identified only to the genus level, and further analysis, such as multilocus sequence analysis (MLSA) using various housekeeping genes or whole-genome sequencing (WGS), is required to accurately define the taxonomic affiliations of Vibrio isolates, especially at the species level [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…; Al‐saari et al. ). However, some members of the genus Vibrio are also opportunistic pathogens that have been associated with infections in humans and marine animals (Austin ).…”
Section: The Family Vibrionaceae: Causative Agents Of Vibriosismentioning
confidence: 98%
“…The optimum temperature was found to be 28 to 40 o C for the degradation of both aliphatic and aromatic compounds. This study indicated that the microbial mats studied from Saudi Arabia are rich in microbes with the ability to degrade oil compounds at very high salinities and temperatures (AL-SAARI et al, 2015;PIETILÄ, 2016).…”
Section: Halophilesmentioning
confidence: 89%
“…The production of industrially important enzymes was found to be higher in both the strains during the growth in lowcost substrate like green gram husk under solid-state fermentation. The purified protease has various applications in detergent industries, food industries and pharmaceutical industries (AL-SAARI et al, 2015;PIETILÄ et al, 2016). Zaki et al (1980) isolated two hundred and four bacterial isolates representing rhizospheric halophiles of five salt marsh plants at Shuaiba lagoon in Saudi Arabia.…”
Section: Halophilesmentioning
confidence: 99%